Solvent‐Free, Metal‐Free, Aza‐Prins Cyclization: Unprecedented Access to δ‐Sultams. Issue 3 (18th December 2012) - Clarisse, Damien; Pelotier, Béatrice; Fache, Fabienne
<x xml:space="preserve">Abstract</x> Aza‐Prins and the pauper: Aza‐Prins cyclization between γ, δ‐unsaturated tosylamines and aldehydes was successfully performed under solvent‐free and metal‐free conditions. When applied to β, γ‐unsaturated sulfonamides, the corresponding δ‐sultams were isolated in good yields (see scheme). This approach constitutes a new route to cyclic sulfonamides.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>